PENGARUH POLA ASUH ORANGTUA TERHADAP KECERDASAN EMOSI ANAK USIA DINI: Studi Siswa Kelompok Bermain Permata Hati Desa Dungus Gresik - Nina Nuriyah Ma'arif; Mufatichatus Zulia (Atthiflah: Journal of Early Childhood Islamic Education, 2021)
This article examines the effect of the pattern of parenting conducted by parents early childhood's emotional intelligence. The research was conducted using correlational quantitative research methods through distributing questionnaires to 23 parents and students of the Permata Hati Play Group in Dungus Village, Cerme District, Gresik in the period from January 14 to March 16 2020. The findings have revealed there is a significant influence between the patterns of parenting on emotional intelligence of early childhood in Play Group of Permata Hati. In this regards, the three distinct parenting styles used by parents, that is authoritarian, permissive, or authoritative, have affected the early childhood's emotional intelligence. Additionaly, there are 12 students were raised by an authoritarian parenting style from their parents, 6 students raised by a permissive parenting style, and 5 students raised through an authoritative parenting strategies.